Zone of Proximal Development: Evolution of the Concept - Zaretsky, V.K. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The main idea of ​​the article is to trace the development and use of the concept of zone of proximal development (ZPD) in the works of Russian psychologists since its introduction into the conceptual apparatus of cultural-historical psychology by L.S. Vygotsky. The article consists of three parts. The first is devoted to the definition of the concept of ZPD, in which the contradictions between the ideas of the author of the concept and the interpretations of it by other authors are analyzed. The "classical definition" of ZPD is supplemented by the ideas of L.S. Vygotsky, expressed by him in other works. The other two parts of the article are devoted to changes in the methodological functions of the concept at different stages of its development: from an explanatory principle to the subject of research, and from the subject of research to a methodological means for the construction of new subjects of practice-oriented technologies. The general trend is to expand the areas of application of the ZPD concept, to go beyond the initial tasks of explaining and theoretically justifying the special connection between learning and development, and beyond the problems of interaction between a child and an adult. Particular attention is paid to the helping activity of an adult (teacher, psychologist, parent, etc.): the main question is how to help in order to contribute to the development. It is shown that the concept of ZPD is now used in psychotherapy and practice of working with adults with developmental disorders, i.e. it becomes the link between education (learning), development and mental health. Основной замысел статьи - проследить траекторию развития и использования понятия зона ближайшего развития (ЗБР) со времени его введения в концептуальный аппарат культурно-исторической психологии Л.С.Выготским по материалам работ отечественных психологов. Статья включает три раздела. Первый посвящен проблеме определения понятия ЗБР, в котором анализируются противоречия в представлениях самого автора понятия и трактовках понятия другими авторами. «Классическое определение» ЗБР дополняется идеями Л.С.Выготского, высказанными им в других работах. Два других раздела статьи посвящены изменениям методологических функций понятия на разных этапах его развития: от объяснительного принципа к предмету исследования, и от предмета исследования к методологическому средству построения новых предметов практико-ориентированных технологий. Общая тенденция заключается в расширении областей применения понятия ЗБР, выходе использования понятия за рамки исходных задач объяснения и теоретического обоснования особой связи обучения и развития, за рамки проблем взаимодействия ребенка и взрослого. Особое внимание уделяется помогающей деятельности взрослого (учителя, психолога, родителя и др.): главный вопрос, как помогать, чтобы помощь способствовала развитию. Показано, что понятие ЗБР начинает использоваться в психотерапии и практике работы со взрослыми людьми с нарушениями развития, т.е. оно становится связующим звеном между образованием (обучение), развитием и психическим здоровьем.